Cognitive approach to developing the intelligent modules of organizational and technical systems - V. M. Trembach (Открытое образование (Москва))
The aim of the study is intelligent modules of organizational-technical systems (OTS) for solving the task of purposeful behavior taking into account features to operate the object in a rapidly changing external environment. A widely used computing paradigm contains inherent symbolic submissions of information and their processing with algorithms focused on the logic and combinatorics of procedures. This computer approach in solving some intellectual tasks is inferior to the man. One of the approaches to study complex tasks can be the use of a simpler model task. For such models, the article investigates the possibility of using the cognitive approach that can be used in the intelligent modules of OTS for solving tasks of purposeful behavior. In order to solve the task of purposeful behavior taking into account features to operate the object in a rapidly changing external environment a cognitive approach to cybernetic systems as intelligent modules of OTS can be used. The author considered the cybernetic approach to the evolution and use of simple model systems with purposeful behavior. A cognitive approach includes plenty of problems. The solution of these problems is connected with the methods, taking into account cognitive aspects referring to processes of perception, thinking, knowledge, explanations and understanding. In a system with a simple model the issues of categorization, the role and place of the Gestalt, the formation of the characteristic values as an important element of cognitive semantics are considered. In further studies it is necessary to pay due attention to the knowledge of cybernetic systems, their submissions, storage, processing, interpretation and production of new knowledge. As a result of the research, the structure of a cybernetic system with a simple model of behavior is proposed. This system is able to solve relatively simple tasks of purposeful behavior. When adding modules, providing recognition of primitive images (geometrical shapes, objects), speech recognition and the formation of voice messages, the cybernetic system is capable to form new signs about the outside world. Using such signs and new controlling actions, the robot can build a more complex interaction with reality. A new system (the robot KSUKHA) allows considering separate categories (the beginnings of the categories) for the further use. Separate categories can become the prototype categories for the future and distant descendants of this cybernetic system (robot) in this evolutionary tree. Application of the considered approach will allow us to come to the solution of tasks of forming categories, and in future to form basic categories to use cognitive mechanisms of human thinking. These mechanisms can be applied in cybernetic systems for solving the tasks of purposeful behavior.